Imágenes y cuerpos del ñandú (Rhea americana) en las celebraciones de los qom: Paisaje, caza y fiesta en el Gran Chaco sudamericano - Robledo, Emilio (2024)
Based on the ethnography of qom (toba) communities living on the right bank of the middle Bermejo River, in the ArgentineChaco, I address the relationship of this people with the ñandú (Rhea americana), a bird native to South America and closelylinked to the hunting tradition in the Gran Chaco. I argue that beyond the hunting activity, this relationship is inscribed in the Chaco landscape, in the memories, cosmology and celebrations of the qom people. This case is framed by the contemporary anthropological debate on the classic opposition between practices and ethos of domestication and hunting, that I approach from the context of indigenous feasts and their ability to congregate in the same space-time human relations and prominent links with plant and animal species. I conclude that the qom’s proximity to the images and body of ñandú, beyond turning the bird into an object of human hunting or significance, allowed them to understand the way of dealing with transformations configured by the alternation between abundance and scarcity, as extremes that shape the landscape and life in the Chaco.